Faktor yang berhubungan dengan Konsumsi Makanan cepat Saji pada Mahasiswa di Institusi Kesehatan Helvetia Medan - Evi Ranggayuni; Nuraini Nuraini (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Fast food is a type of food that is easy to serve, serve, practical, or simple processed. Based on the results of a preliminary survey conducted at the Helvetia Institute of Health, Medan. The results of interviews were conducted from 205 respondents who were undergraduate students of Public Health in the even semester of 199 respondents who consumed fast food and only 6 people who consumed healthy food and brought lunch from home. They prefer fast food because it is easy to find and more practical. This study was to determine the factors associated with consumption of fast food (fast food) in public health undergraduate students at the Helvetia Institute of Health, Medan. This study was a survey analysis with a cross sectional design. The population of this study were 205 undergraduate students of public health at the Helvetia Health Institute, Medan. The sample in this study was 67 respondents. Data analysis used univariate and bivariate analysis with chi-square test. This study is the factors related to the consumption of fast food (fast food) at Helvetia Institute of Health, Medan a attitudes, knowled, and peers.